CONTRIBUTION TO THE UNDERSTANDING OF SERBIAN-ALBANINAN RELATIONS (Heritage, 2024)
The main population in Kosovo and Metohija, during the medieval Serbian state, conssisted of Serbs. It will remain so after the occupation of these areas by the Turks. According to historical sources on the structure of the population in the Balkans at the beginning of the 16th centtury, it can be seen that the rural life in Kosovo is entirely Serbian. There were no Arbanas, not only Muslims but also Christians, in Kosovo at that time, and not until the 17th century.The Albaninan colonization of Kosovo and Metohija, according to historical sources and anthropogeographica I reconstructions, began in the 16th century, but it was not characterized by a mass that would change the ethnographic picture ot these areas. Mass colonization occurred at the end of the 17th century, as a result of the difficult circumstances caused by the Austrian-Turkish war. From this time began not only the settlement of the Albaninan population, but also the expulsion of the Serbian people from these areas. During the 18th century, even more so in the 19th century, the intention that this expulsion has a systemic and planned character is clearly recognized, in order to fully settle and appropriate these areas. Islamization was of the greatest help to them, because it made them Turkish wards and a tool used by the Turkish state against its Christian subjects. Islamization was a way for the Christian population to be assimilated not only into Muslims, but also to be Albanianized.
Keywords: Serbs, Albanians, Illyrians, Kosovo, Metohija, Turks, Islamization, assimilation, migrations